Reading Sara Pujol Russell’s Poetry of Contemplation and Connection - Anita M. Hart (Studies in 20th & 21st Century Literature, 2012)
Sara Pujol Russell’s poetry captures a process of expanding consciousness and personal renewal. Through contemplation and attention to nature, the poet-speaker in her works generates a sense of connection that moves her beyond daily concerns. Pujol’s poetry is both metaphysical and also different in that it resists easy classification and is not representative of mainstream trends. This essay approaches the distinctiveness of Pujol’s work by studying selected poems from her third book of poetry in Spanish, Para decir sí a la carencia, sí a la naranja, al azafrán en el pan (2004) ‘To Say Yes to Lack, Yes to the Orange, to the Saffron in the Bread.’ Incorporating philosopher María Zambrano’s thoughts on contemplation, it shows Pujol’s poet-speaker establishing a connection with nature and spirit, experiencing a heightened consciousness, and searching for expression. The poetic language is characterized by vision, intimacy, enigma, and contradiction. In its subjective, intuitive way, Pujol’s work reveals the poet-speaker’s winding path of discovery and challenges the reader to look closely inside and outside in engaging life’s mysteries.
Keywords: Sara Pujol Russell; poetry; consciousness; nature; contemplation; spirit; mystery; mysterious; enigma